EVALUASI KEBIJAKAN PENDIDIKAN INKLUSI DALAM PERATURAN BUPATI NOMOR 10 TAHUN 2013 TENTANG PENYELENGGARAAN PENDIDIKAN INKLUSI DI SEKOLAH DASAR NEGERI SUKOHARJO KABUPATEN REMBANG - Roby Yunata; Zainal Hidayat; Sundarso Sundarso; Hartuti Purnaweni (Journal of Public Policy and Management Review, 2016)
Inclusive education is an educational services for children with special needs to study with normal children (regular) in the same study group and school. The purpose of this reaserch is to evaluate the implementation of policy of inclusive education in the State Elementary School of Sukoharjo Rembang which is measured on three indicators that are divided into seven sub-indicators, that is: (aspect), Input (curriculum, teachers and educators, facilities and infrastructure, and financing ), process (guidance and supervision and cooperation) and Output (learners). The Researchers analyzed the of factors constraints faced by the government of Rembang, State Elementary School of Sukoharjo and society. Evaluaasi inclusion policies in the education system meant to see if it is in accordance with the policy goals of providing the widest possible opportunity; quality education services; and educational services are not discriminatory. Education Evaluation research results Inclusion State Primary School Sukoharjo Rembang still encountering many obstacles on the aspects that are, among others: there are discrimination educational services, educators Welfare has not been fully considered. Availability of facilities still lacking and there is no understanding that cooperation between the Government of Rembang and the community about the rise and graduation for children with special needs.